(untitled) (Philological Studies, 2019)
The nations of Southeast Europe have been exchanging ideas in all areas of cultural life (music, folklore, dance, literacy, literature, artistic expression, etc.) ever since ancient time. Today this communication is even intensive because of the development in technological, economic, social, and political conditions. Yet, it also is marked by certain difficulties associated with the tendency to systematically identify the culture and cultural identity of all countries individually, or even to impose a new identity, or to forbid the free identity expression of whole nations. All of this is done very diplomatically and skillfully hidden behind alleged contemporary democratic values. But the real reason for such tendencies is the aim for a better national position in globalization processes. In doing so, the challenges of the new time are neglected, such as the fact that an increasing amount of cultural entities of countries are not perfectly homogeneous, stable and immutable; but that they are mixed, fluid, interconnected and directed to genuine common communication and support. In order to overcome such negative tendencies and to improve communication among the countries of Southeastern Europe, in this paper, I propose to apply principles of contemporary intercultural dialogue, which are reflected in: understanding of the process of communication between different cultures; identifying challenges arising from differences of one’s own perceptions; sharing common cultural values; acquiring and developing knowledge, skills and attitudes that will increase the ability for intercultural communication and action that is the opposite of the narrow nationalistic commitments arising in this region.